2021
DOI: 10.3390/pharmaceutics13122093
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Liposomal Formulations for Ocular Delivery of Thymoquinone: In Vitro Evaluation in HCEC-2 e HConEC Cells

Abstract: Thymoquinone (TQ) is the main constituent of Nigella sativa L. essential oil. In vitro studies have shown its protective effect against H2O2-induced oxidative stress in human retinal pigment epithelium cells, and in vivo experiments have demonstrated its effect in decreasing corneal neovascularization and reducing the inflammation in an experimental dry eye model in mice. Its therapeutic use is limited by poor bioavailability, low solubility, and scarce permeability. In this study, two liposomal formulations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…On the basis of our findings, we hypothesize that the liposomal formulation of the ocular spray tested is responsible for the reduction of the toxicity of the antiseptic Biosecur on conjunctival and corneal epithelial cells in vitro. Our hypothesis is also supported by previous studies which reported that liposomal formulations are able to reduce the toxicity of different drugs for ocular tissues [ 18 , 19 ] and conjunctival and corneal cells in vitro [ 20 ]. Liposomes have in fact some advantages over most ophthalmic delivery systems: they are biodegradable, biocompatible, relatively nontoxic, and they can provide an intimate contact with the corneal surface [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…On the basis of our findings, we hypothesize that the liposomal formulation of the ocular spray tested is responsible for the reduction of the toxicity of the antiseptic Biosecur on conjunctival and corneal epithelial cells in vitro. Our hypothesis is also supported by previous studies which reported that liposomal formulations are able to reduce the toxicity of different drugs for ocular tissues [ 18 , 19 ] and conjunctival and corneal cells in vitro [ 20 ]. Liposomes have in fact some advantages over most ophthalmic delivery systems: they are biodegradable, biocompatible, relatively nontoxic, and they can provide an intimate contact with the corneal surface [ 21 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, cationic FK506 liposomes were proven to prolong ocular retention time and increase FK506 amount in the cornea; at the same time, this treatment alleviated the signs of dry eye and reduced the expression of inflammatory factors in vitro and in vivo. Landucci et al (2021) developed a thymoquinone-loaded liposome and found that it could reduce the toxicity at high dose in HCEC-2 cells. Huang et al (2017) constructed the liposome encapsulating montmorillonite and betaxolol hydrochloride to treat glaucoma and found that liposomal formulation could effectively reduce cytotoxicity of betaxolol hydrochloride.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is the first bibliometric study of mTOR in neuroscience, there are some limitations that have been reported in other bibliometric study papers ( Chen et al, 2020 ; Landucci et al, 2021 ; Ma et al, 2021 ). The deadline for publication of this study is 31 December 2021, but the WoSCC will be updated constantly.…”
Section: Limitationsmentioning
confidence: 94%